Economics of information and knowledge, selected readings - Lamberton, D. M. (Harmondsworth, Eng.: Penguin Books, 1971)
This book comprise of papers on the economics of knowledge written by renowned economist comprising of seven parts namely: two surveys; economic organisation; information and efficiency; information policy; international aspects; business planning and conclusion. Topics include: The economics of knowledge and the knowledge of economics, by K.E. Boulding; Economics of inquiring, communicating, deciding, by J. Marschak; The economics of information, by G.J. Stigler; An information version of pure competition, by R.A. Jenner; Information networks in labour markets, by A. Rees; Information without profit, by G. Tullock; Economic welfare and the allocation of resources for invention, by K.J. Arrow; Information and efficiency: another viewpoint, by H. Demsetz; The tax treatment of research and innovative investment, by R.E. Slitor; The benefit and cost of government support for research and development: a case study, by K. Grossfield and J.B. Heath; The patent system, by A. Silbertson; Policy for the transfer of results, by Organisation for Economic Co-operation and Development; International trade and technical change, by M.V. Posner; International trade in inputs and outputs, by R.E. Baldwin; Long-range formal planning in perspective, by B.S. Loasby; A scarce resource called curiosity, by D. Davies.--Technological forecasting in corporate planning, by E. Jantsch; and Information, rationality, and free choice in a future democratic society, by M. Shubik.
Includes bibliography and index.
lje 21/1/19
Loans
Keywords: Information theory in economics; Economics